Coordinated Hibernation of Transcriptional and Translational Apparatus during Growth Transition of Escherichia coli to Stationary Phase - Hideji Yoshida (American Society for Microbiology, 2018)
ABSTRACT In the process of Escherichia coli K-12 growth from exponential phase to stationary, marked alteration takes place in the pattern of overall genome expression through modulation of both parts of the transcriptional and translational apparatus. In transcription, the sigma subunit with promoter recognition properties is replaced from the growth-related factor RpoD by the stationary-phase-specific factor RpoS. The unused RpoD is stored by binding with the anti-sigma factor Rsd. In translation, the functional 70S ribosome is converted to inactive 100S dimers through binding with the ribosome modulation factor (RMF). Up to the present time, the regulatory mechanisms of expression of these two critical proteins, Rsd and RMF, have remained totally unsolved. In this study, attempts were made to identify the whole set of transcription factors involved in transcription regulation of the rsd and rmf genes using the newly developed promoter-specific transcription factor (PS-TF) screening system. In the first screening, 74 candidate TFs with binding activity to both of the rsd and rmf promoters were selected from a total of 194 purified TFs. After 6 cycles of screening, we selected 5 stress response TFs, ArcA, McbR, RcdA, SdiA, and SlyA, for detailed analysis in vitro and in vivo of their regulatory roles. Results indicated that both rsd and rmf promoters are repressed by ArcA and activated by McbR, RcdA, SdiA, and SlyA. We propose the involvement of a number of TFs in simultaneous and coordinated regulation of the transcriptional and translational apparatus. By using genomic SELEX (gSELEX) screening, each of the five TFs was found to regulate not only the rsd and rmf genes but also a variety of genes for growth and survival. IMPORTANCE During the growth transition of E. coli from exponential phase to stationary, the genome expression pattern is altered markedly. For this alteration, the transcription apparatus is altered by binding of anti-sigma factor Rsd to the RpoD sigma factor for sigma factor replacement, while the translation machinery is modulated by binding of RMF to 70S ribosome to form inactive ribosome dimer. Using the PS-TF screening system, a number of TFs were found to bind to both the rsd and rmf promoters, of which the regulatory roles of 5 representative TFs (one repressor ArcA and the four activators McbR, RcdA, SdiA, and SlyA) were analyzed in detail. The results altogether indicated the involvement of a common set of TFs, each sensing a specific environmental condition, in coordinated hibernation of the transcriptional and translational apparatus for adaptation and survival under stress conditions.